2010
DOI: 10.5539/ijbm.v5n12p141
|View full text |Cite
|
Sign up to set email alerts
|

Career Stage Effect on Organizational Commitment: Empirical Evidence from Indian Banking Industry

Abstract: This study examines the career stage effect on organizational commitment of bank employees. The subjects included 660 clerical and managerial staff of Indian banks operating in the state of Punjab in northern India. Organizational commitment has been measured by Meyer et al.'s (1993) Organizational Commitment Scale. Career stages were identified by each respondent's self-reported age, and tenure in the organization. Results of the study revealed significant differences in organizational commitment across care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 58 publications
3
23
0
4
Order By: Relevance
“…This implies that it is important for managers to focus on improving the communication satisfaction level of younger employees, which in turn will increase their organizational commitment. These findings were supported by the study done Kaur and Sandhu (2010), who reported that older workers tend to have higher organizational commitment due to the changes in their environment and life experiences.…”
Section: Discussionsupporting
confidence: 72%
“…This implies that it is important for managers to focus on improving the communication satisfaction level of younger employees, which in turn will increase their organizational commitment. These findings were supported by the study done Kaur and Sandhu (2010), who reported that older workers tend to have higher organizational commitment due to the changes in their environment and life experiences.…”
Section: Discussionsupporting
confidence: 72%
“…These theories pronounce, people pass through specific career stages during their life span. Stages usually are, based on chronological age though the age ranges assigned for each stage have varied considerably between empirical studies (Kaur & Sandhu, 2010). The common point of them is that stages are mostly categorized as early, middle, and late.…”
Section: Discussionmentioning
confidence: 99%
“…The common point of them is that stages are mostly categorized as early, middle, and late. This categorization partially corresponds to the exploration, establishment, and maintenance stages of Super's theory (Kaur & Sandhu, 2010). Ornstein et al (1989) argued that career stages can be based either on age or on organizational, positional or professional tenure.…”
Section: Discussionmentioning
confidence: 99%
“…While defined the emotional commitment as the employee's relation and with its goals, and the employee's desire to keep working with his or her organization [44]. Another one defined the emotional commitment as the extent to which employees feel committed towards their organization by virtue of balancing the costs associated with leaving the job, emotional commitment is emotional bond with organization and employee's belief in the values of organization [45].…”
Section: Dimensions Of Organizational Commitmentmentioning
confidence: 99%